A new species of Libellula Linnaeus, 1758, from the Cuatro Ciénegas basin, Coahuila, México (Anisoptera: Libellulidae) - Ortega-Salas, Héctor; González-Soriano, Enrique (Zootaxa, 2015)
A new species of Libellula is described from specimens collected in the most interesting area of Cuatro Ciénegas, Coahuila, México. Libellula coahuiltecana sp. nov. is similar in color and morphology to L. needhami Westfall with which it co-occurs locally. It differs from the latter by having conspicuous orange spots on base of wings and nodal area, and costal, subcostal, and wing tip areas slightly infumated with the same color. Other differences exist in the morphology of the secondary genitalia of males and the shape of the vulvar plate of female.